2017
DOI: 10.1021/jacs.7b05555
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Studies on the Effects of Monomer Planarity on Covalent Organic Framework Formation

Abstract: We report the synthesis of one new boronate ester-based covalent organic framework (COF) and two new covalent organic polymers (COPs) made with fluoranthene-containing monomers and hexahydroxytriphenylene. The structure of the monomer heavily influences whether this material forms a highly ordered mesoporous material (COF) or an amorphous, microporous material (COP). The synthesis of the fluoranthene monomers was carried out using a divergent strategy that allows for systematic structural variation and the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 53 publications
0
56
0
Order By: Relevance
“…2D‐CN‐PPV‐2 with the BPDA spacer only shows two major reflections in the PXRD pattern, indicating moderate crystallinity (Figure b). This observation could be explained by the lower shape persistency of the starting monomers, leading to weaker interlayer π–π stacking and therefore worse alignment in the plane . The structures of all the 2D‐CN‐PPV s were optimized in typical eclipsed (AA), staggered (AB), and slipped eclipsed (slip‐AA) π–π stacking arrangements by using the density functional tight binding method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2D‐CN‐PPV‐2 with the BPDA spacer only shows two major reflections in the PXRD pattern, indicating moderate crystallinity (Figure b). This observation could be explained by the lower shape persistency of the starting monomers, leading to weaker interlayer π–π stacking and therefore worse alignment in the plane . The structures of all the 2D‐CN‐PPV s were optimized in typical eclipsed (AA), staggered (AB), and slipped eclipsed (slip‐AA) π–π stacking arrangements by using the density functional tight binding method.…”
Section: Resultsmentioning
confidence: 99%
“…This observation could be explained by the lower shape persistency of the starting monomers, leading to weaker interlayer p-p stacking and therefore worse alignment in the plane. [13] The structures of all the 2D-CN-PPVsw ere optimized in typicale clipsed (AA), staggered (AB), and slipped eclipsed (slip-AA) p-p stacking arrangements by using the density functional tight binding method.I th as been found that the experimental PXRD patterns of all 2D-CN-PPVsa re matched well with the simulated ones derived from the eclipsed (AA) p-p stacking arrangement ( Figures S4-1-S4-3, in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, COFs have been intensively investigated in the fields of gas adsorption and separation, catalysis, energy storage and conversion, and electronic devices . In general, the application region of COFs depends on their textural peculiarity, such as functional units, pore size and surface area . In addition, some anthropogenic factors, including reagent concentrations, reaction conditions, purification procedure, degassing process, and so on, also influence the gas sorption capacity and corresponding functions of COFs .…”
Section: Introductionmentioning
confidence: 99%
“…[10] In general, the application regiono fC OFs depends on their textural peculiarity,s uch as functional units,p ore size and surface area. [11] In addition, some anthropogenic factors, including reagent concentrations, reactionc onditions, purificationp rocedure, degassingp rocess, and so on, also influence the gas sorption capacitya nd corresponding functions of COFs. [12,13] Therefore, it is reasonable that different gas isotherms were reproduced by different ex-perimental groups for the same material at the same conditions.…”
Section: Introductionmentioning
confidence: 99%